Uncloneable Quantum Encryption via Random Oracles - Lord, Sébastien (Université d'Ottawa / University of Ottawa, 2019)
One of the key distinctions between classical and quantum information is given by the no-cloning theorem: unlike bits, arbitrary qubits cannot be perfectly copied. This fact has been the inspiration for many quantum cryptographic protocols. In this thesis, we introduce a new cryptographic functionality called uncloneable encryption. This functionality allows the encryption of a classical message such that two collaborating but non-communicating adversaries may not both simultaneously recover the message, even when the encryption key is revealed. We achieve this functionality by using Wiesner’s conjugate coding scheme to encrypt the message. We show that the adversaries cannot both obtain all the necessary information for the correct decryption with high probability. Quantum-secure pseudorandom functions, modelled as random oracles, are then used to ensure that any partial information that the adversaries obtain does not give them an advantage in recovering the message.
Keywords: Quantum Cryptography